(Reseña) Jody Pavilack, "Mining for the Nation: The Politics of Chile’s Coal Communities from the Popular Front to the Cold War" - Salgado Muñoz, Alfonso (Historia, 2012)
Las "Reseñas bibliográficas" no contemplan resumen.